Assessing the effectiveness of waste minimization methods in solid waste reduction at the source by manufacturing firms in Malaysia - Mallak, Shadi Kafi; Ishak, Mohd Bakri; Mohamad Kasim, Mohamad Roslan; Abu Samah, Mohd Armi (HARD Publishing, 2015)
Manufacturing industries in Malaysia play a fundamental role in economic growth and enhancing the populations standard of living.However, a huge quantity of industrial wastes is generated daily, exacerbating landfill disposal issues. Waste minimization as the most sustainable approach of waste handling contributes to a significant reduction of waste. In Malaysia, practicing waste minimization by manufacturing firms is not very common. Thus, this study attempted to determine the most commonly practiced methods of minimization by manufacturing firms in Malaysia.